An Analysis of Directive Speech Acts by The Main Characters in Jurassic World Dominion Movie - Nensi Asma Yulia Putri; Rahma Yanti; Irsyad Shabri; Yalmiadi; Thiska Septa Maiza (Prologue: Journal on Language and Literature, 2023)
This study aims to determine the types of Directive Speech Acts used by the main characters in the movie of Jurassic World Dominion (2022). This study applies the theory of Searle (1976) to the types of Directive Speech Acts. The subject of this study is the conversation of the main characters in the movie. This study used a qualitative descriptive approach and Simak Bebas Libat Cakap (SBLC) technique to gather and analyze the data. The results of this study reveal two things,first, Question ranks the highest score with 46 utterances (57,5%), because the genre of the movie is action automatically every conversation will be followed by action from the listener. Meanwhile, Permission 2 utterances (3.7%) rank the lowest score, because the movie is about an adventure and there are not too many formal words found. Finally, Permission is the least commonly used because most of the dialogue in this movie is about adventure, and the relationships between the players are closely intertwined without any age restrictions.